2021
DOI: 10.5114/biolsport.2021.109952
|View full text |Cite
|
Sign up to set email alerts
|

The effects of COVID-19 lockdown on jumping performance and aerobic capacity in elite handball players

Abstract: The aim of this research was to analyse the capacity of a home-based training programme to preserve aerobic capacity and jumping performance in top-level handball players during the COVID-19 lockdown. Eleven top-level male handball players from the same team participated in the study. A submaximal shuttle run test and a counter-movement jump test were used to measure the players’ aerobic fitness and lower limb explosive strength, respectively. A 9-week home-based training programme was followed during lockdown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…Detraining during the transition period caused significant performance impairments in a number of physiological and performance measures such as VO2max, time to exhaustion, repeated-sprint ability and Yo-Yo test intermittent-running performance [2,7,8,21]. Moreover, previous studies showed that a structured home-based exercise program during the COVID-19 lockdown was effective in maintaining or improving physical fitness measures such as countermovement jump performance, an indicator of lower extremity explosive strength in elite handball players [22], and youth soccer players [23]. In another study, it was stated that after a 32-week detraining period, caused by the COVID-19 pan-demic lockdown, significant improvements were observed in neuromuscular parameters (vertical jump height, agility, and linear sprints) of young soccer players, depending on maturation-related adaptations [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Detraining during the transition period caused significant performance impairments in a number of physiological and performance measures such as VO2max, time to exhaustion, repeated-sprint ability and Yo-Yo test intermittent-running performance [2,7,8,21]. Moreover, previous studies showed that a structured home-based exercise program during the COVID-19 lockdown was effective in maintaining or improving physical fitness measures such as countermovement jump performance, an indicator of lower extremity explosive strength in elite handball players [22], and youth soccer players [23]. In another study, it was stated that after a 32-week detraining period, caused by the COVID-19 pan-demic lockdown, significant improvements were observed in neuromuscular parameters (vertical jump height, agility, and linear sprints) of young soccer players, depending on maturation-related adaptations [11].…”
Section: Discussionmentioning
confidence: 99%
“…Pucsok et al [23] found that the endurance capacity of young soccer players was moderately deteriorated after completing a 13-week home-based training routine during the COVID-19 lockdown. In additon, recent studies stated that cardiorespiratory endurance or VO2max, determined by the maximum mean velocity reached in a multistage 20-metre shuttle run test, was decreased in elite handball players [24], youth soccer players [4,25], female soccer players [26], and professional soccer players [22] due to non-specific and insufficient stimuli caused by a home-based exercise program during the COVID-19 lockdown. Furthermore, contrary to neuromuscular parameters (countermovement jump, change of direction ability, and 30 m sprint performance), a recent study was conducted by Alvurdu et al [9] on young soccer players aged 15-18 which noted that the highest performance loss was observed in aerobic capacity measured by the YYIRTL-1 test after a long-term detraining period of 15 weeks due to the COVID-19 lockdown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study conducted on handball players during the COVID-19 lockdown, although a structured 9-week home-based exercise program preserved the neuromuscular performance of the athletes, it was insufficient to maintain their aerobic capacity [48].…”
Section: Aerobic Capacitymentioning
confidence: 99%
“…This has led to a series of restrictions, which from a pathophysiological point of view, may affect the athlete's performance in the short and long term. The restrictions basically affect training and eating habits, disturbing physical condition, as well as psychological behavior and general health status [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%